Trust, culture, and territorial development - Kis Mária (Jelenkori társadalmi és gazdasági folyamatok, 2009)
Some researchers think that economic life is inseparable from culture, i.e., the "irrational" values associated with moral, public spirit, family, and religion, thus the latter manifests itself in neo-liberal economics that predominantly relies on interests and making rational choices only to a limited extent. Therefore, modern societies see preservation or creation of high-level social trust and social capital as their major task, since its lack is capable of hindering economic growth in a way similar to that of a deficit in physical capital. The above considerations provide a ground for explaining the success of certain settlements and the failure of others to succeed.